2021
DOI: 10.1136/bmjopen-2020-046660
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with attendance at screening for breast cancer: a systematic review and meta-analysis

Abstract: ObjectiveAttendance at population-based breast cancer (mammographic) screening varies. This comprehensive systematic review and meta-analysis assesses all identified patient-level factors associated with routine population breast screening attendance.DesignCINAHL, Cochrane Library, Embase, Medline, OVID, PsycINFO and Web of Science were searched for studies of any design, published January 1987–June 2019, and reporting attendance in relation to at least one patient-level factor.Data synthesisIndependent review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 87 publications
3
22
0
1
Order By: Relevance
“…Indeed, although participation decreased among all socioeconomic groups, this decline was greater in low-income areas. A systematic review of studies conducted before the pandemic reported lower participation in low-income groups, immigrants, nonhomeowners, and women with a previous false-positive result ( Mottram et al, 2021 ). Furthermore, studies recently published in the United States have reported a decrease in participation, especially in underserved ethnic groups, with lower socioeconomic status, lack of insurance and longer travel time ( Amram et al, 2021 ; Miller et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, although participation decreased among all socioeconomic groups, this decline was greater in low-income areas. A systematic review of studies conducted before the pandemic reported lower participation in low-income groups, immigrants, nonhomeowners, and women with a previous false-positive result ( Mottram et al, 2021 ). Furthermore, studies recently published in the United States have reported a decrease in participation, especially in underserved ethnic groups, with lower socioeconomic status, lack of insurance and longer travel time ( Amram et al, 2021 ; Miller et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, interventions that have been developed to improve access to breast screening in general populations, for example, using social media engagement ( 49 ), may not be appropriate or even reach some of the morbidity cluster groups that have the greatest odds of non-attendance. Finally, because of the mixed reporting in the studies included in this review of potential sociodemographic confounders, such as ethnicity and deprivation ( 50 ), it is unclear whether interventions developed specifically to reduce inequity of access for these reasons would be effective if individuals also have morbidities. The identification of such research gaps can subsequently form the development and testing of theory-based interventions to increase equity of access to breast screening.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it may well reflect a real phenomenon. A systematic review of studies conducted before the pandemic reported lower participation in low-income groups, immigrants, non-homeowners, and women with a previous false-positive result (24). Furthermore, studies recently published in the US have reported a decrease in participation, especially in underserved ethnic groups, with lower socioeconomic status, lack of insurance and longer travel time (25,26).…”
Section: Discussionmentioning
confidence: 99%